Surveying fundamentals - McCormac, Jack C. (Englewood Cliffs, N.J. : Prentice Hall, 1991)
This book is about: Measurement; Distance corrections and miscellaneous taping operations; Electronic distance measuring instruments; Differential leveling; ...
Keywords: Surveying; Surveying